(untitled) (Olhar de Professor, 2022)
The present experience report seeks to share learning strategies built in the year 2020, in public educational spaces, in the countryside of Rio Grande do Sul. In the midst of the challenging context, we sought to outline possibilities for the construction of pedagogical practices for remote teaching in Early Childhood Education and Elementary Education (First and late years). The development of these practices was based on the methodology of projects, subsidized by BNCC and RCG; having as its main tool playing with elements of nature, meeting the daily experiences of children. The main theoretical contributions were triggered by Andreola (2016), Freire (1992, 1993, 1996, 1997), Redin (2017), Vygostsky (2007) and others. The monitoring since the planning, development and feedback of practices, demonstrated the genuine possibility of developing meaningful, playful and interactionist learning; considering different social and economic contexts.